Journey : an illustrated history of travel - Adams, Simon (Transport consultant) (DK, Penguin Random House, 2017)
"An illustrated account of human movement, travel, exploration, and scientific discovery-from the first trade networks in ancient Sumer to the epic Voyager missions. Human journeys arise from all manner of impulses, from migration and the search for food, to pilgrimages, trade, scientific curiosity, or simply the quest for adventure. Journey traces each through lively accounts, alongside the biographies of conquerors, explorers, and travelers; stories of technological innovation; literary journals; and works of art. Themed spreads and feature panels capture the romance of travel with evocative accounts, archive images, historic maps, and artifacts, while catalog spreads add glamour and nostalgia, showcasing objects and documents associated with the rise of travel, such as postcards and passports. A textured cover with a picture-perfect image and shiny finishes make it ideal for gift-giving. Produced in association with the Smithsonian Institution." -- ONIX annotation.